2003
DOI: 10.1097/00005176-200304000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Follow-Up of Exocrine Pancreatic Function in Pancreatic Sufficient Cystic Fibrosis Patients Using the Fecal Elastase-1 Test

Abstract: The decline of EPF in patients with CF appears more frequently during the first months and years of life. However, late PS to pancreatic-insufficient (PI) conversion is also possible. The appearance of maldigestion is preceded by the decrease of fecal E1 concentration. Thus, the fecal E1 test is a helpful screening tool for the longitudinal assessment of declining EPF in PS patients with CF to demonstrate pancreatic deterioration. In suspected patients, fecal fat excretion should be assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 16 publications
2
39
0
Order By: Relevance
“…29 This test is suitable for longitudinal follow-up of exocrine function in pancreatic sufficient patients and for deciding the timing of enzyme replacement. 32,33 In conclusion, compared with other indirect tests, fecal pancreatic elastase is a sensitive and specific test of exocrine pancreatic function, though it never attains the sensitivity and specificity of the direct function test. It is clinically valuable as a reproducible marker for severe exocrine pancreatic insufficiency, and it is suitable for longitudinal follow-up of exocrine pancreatic function in cases of suspected chronic pancreatitis and cystic fibrosis.…”
Section: Discussionmentioning
confidence: 92%
“…29 This test is suitable for longitudinal follow-up of exocrine function in pancreatic sufficient patients and for deciding the timing of enzyme replacement. 32,33 In conclusion, compared with other indirect tests, fecal pancreatic elastase is a sensitive and specific test of exocrine pancreatic function, though it never attains the sensitivity and specificity of the direct function test. It is clinically valuable as a reproducible marker for severe exocrine pancreatic insufficiency, and it is suitable for longitudinal follow-up of exocrine pancreatic function in cases of suspected chronic pancreatitis and cystic fibrosis.…”
Section: Discussionmentioning
confidence: 92%
“…When patients are reinvestigated as to pancreatic status, but already taking enzymes, a low EL1 will confirm the need for enzyme treatment without having to stop their treatment. 31 The test is also 32 We consider EL1 the best indirect measure of pancreatic function, and it has superseded other indirect pancreatic function tests for routine use. 33 …”
Section: Identification Of a Pancreatic Lesionmentioning
confidence: 99%
“…Walkowiak measured Fel-1 in a group of 184 patients with cystic fibrosis for 5 years. Only 35/184 were pancreatic-sufficient at the beginning of the study, and 8/35 demonstrated a falling Fel-1 level and subsequent steatorrhea [37]. Similarly, Cartmell et al described two patients with chronic pancreatitis who showed a steady decline in Fel-1 over a 7-month follow-up period [38].…”
Section: Discussionmentioning
confidence: 95%